2020
DOI: 10.1186/s13613-020-00776-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety, and resource utilisation of active mobilisation of patients on extracorporeal life support: a prospective observational study

Abstract: Background There is scarce evidence on the feasibility, safety and resource utilisation of active mobilisation in critically ill patients on extracorporeal life support (ECLS). Methods This prospective observational single-centre study included all consecutive critically ill patients on ECLS admitted to an academic centre in Germany over a time period of one year. The level of mobilisation was categorised according to the ICU Mobility Scale (IMS). Primary outcome was complications during mobilisation. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…Braune et al reported the feasibility and safety of early mobilization of patients requiring extracorporeal life support when performed by a multidisciplinary team comprised of critical care nurses, physiotherapists, perfusionists, intensive care physicians, and cardiac surgeons. 15 Similarly, Perme et al has reported benefits in early physical therapy in LVAD patients. 16 For patients requiring intra-aortic balloon pump support, it is possible to place the catheter via the axillary artery, facilitating ambulation with reasonable outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Braune et al reported the feasibility and safety of early mobilization of patients requiring extracorporeal life support when performed by a multidisciplinary team comprised of critical care nurses, physiotherapists, perfusionists, intensive care physicians, and cardiac surgeons. 15 Similarly, Perme et al has reported benefits in early physical therapy in LVAD patients. 16 For patients requiring intra-aortic balloon pump support, it is possible to place the catheter via the axillary artery, facilitating ambulation with reasonable outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Braune et al. reported the feasibility and safety of early mobilization of patients requiring extracorporeal life support when performed by a multidisciplinary team comprised of critical care nurses, physiotherapists, perfusionists, intensive care physicians, and cardiac surgeons 15 . Similarly, Perme et al.…”
Section: Discussionmentioning
confidence: 99%
“…Only 583 reported potential safety events, for a cumulative incidence of 2.6%, such as oxygen desaturation, hemodynamic changes, and removal or dysfunction of intravascular catheter [78]. Other safety events were falls and cardiac arrests in a quite small rate [74]. Feasibility and safety of ECMO rehabilitation in the ICU have been also shown during the last decade as shown in Table 1.…”
Section: Rehabilitation In Ecmo Patients-safety Feasibility and Efficacymentioning
confidence: 99%
“…Strength training is an important rehabilitation tool of ICU-AW prevention and treatment in patients on ECMO support. Most exercise training protocols perform both aerobic exercise and strength endurance training [52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Strength training exercises could be either passive in-bed for the early stages of prehabilitation and early mobilization, or active out-of-bed for conscious patients with better neuromuscular conditions and functional capacity.…”
Section: Strength Trainingmentioning
confidence: 99%
See 1 more Smart Citation